The Study of Seeing Characteristic at the UAD Observatory on Procyon, Sirius, Spica, Nunki, Altair, and Vega using Celestron C6-N telescope - Ricka Tanzilla; Yudhiakto Pramudya; M. Khairul Ardi; Okimustava Okimustava (Jurnal Fisika Indonesia, 2022)
Astronomical observatories can be declared feasible if they have a good condition such as a dark sky, relatively little cloud coverage, relatively low light pollution, and small air turbulence or seeing. The UAD (Universitas Ahmad Dahlan) observatory was measuring the seeing characteristic to assess the feasibility condition. The DIMM method (Differential Image Motion Monitor) was utilized to get the measurement in April, May, and September 2019. The 150 mm diameter Celestron C6-N telescope was used as the instrument to get the star images. The characteristics of a good seeing value on April 10, 2019, are Procyon star with a value of 0.2 arc seconds, and on September 18, 2019, the Vega star with a value of 1.6 arc seconds. Analysis of the seeing characteristic at the UAD Observatory can be used as a reference for observers on star selection, and the operation of the telescope